Adventures of Working Men. From the Notebook of a Working Surgeon - Fenn, George Manville, 1831-1909 (Salt Lake City, UT : Project Gutenberg, 2011)
"Adventures of Working Men: From the Notebook of a Working Surgeon" by George Manville Fenn is a collection of narratives centered around the lives and experiences of working-class individuals, written in the late 19th century. The author, serving as a working surgeon, offers insights into his encounters with various patients, particularly focusing on the unique qualities and stories of working men. This work highlights themes of resilience, faith in medical care, and the harsh realities faced by laborers. The opening of the book introduces the perspective of the surgeon who reflects on his numerous patients, contrasting the straightforward trust of the working man with the often skeptical nature of wealthier patients. He expresses a deep respect for the working-class individuals he encounters, portraying them as strong, hopeful, and deserving of admiration. The surgeon notes that he has gathered his experiences and anecdotes over many years in a notebook, which he now shares as sketches of both ordinary and extraordinary situations faced by these men in their laborious lives. The narratives promise to delve deeper into their stories, showcasing the courage and humanity that often lies hidden beneath their tough exterior. (This is an automatically generated summary.)
Release date is 2011-07-05
Produced by Nick Hodson of London, England
Keywords: Working class -- Fiction; Physicians -- England -- Fiction